2013
DOI: 10.1111/ans.12168
|View full text |Cite
|
Sign up to set email alerts
|

Surgical safety checklists: a review

Abstract: Background: Surgical checklists are designed to improve patient outcomes following surgery. While such checklists have been widely implemented worldwide, few studies examine surgical checklists within an Australian context. For this purpose, we have performed a literature review using data from OECD member nations to determine the effectiveness of surgical checklists in improving patient outcomes and factors that contribute to their successful implementation. Method: The databases, Pubmed, Medline, EMBASE, Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 28 publications
2
65
0
13
Order By: Relevance
“…Ward nurses presenting a summary of the patient's condition and medical history to the surgeon in the OR before surgery. 5. Use of pulse oximetry in the OR and in the recovery ward after surgery, was noted to be valuable but they said they lacked the equipment to do this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ward nurses presenting a summary of the patient's condition and medical history to the surgeon in the OR before surgery. 5. Use of pulse oximetry in the OR and in the recovery ward after surgery, was noted to be valuable but they said they lacked the equipment to do this.…”
Section: Resultsmentioning
confidence: 99%
“…In high income countries it is known that successful implementation requires effective and decisive leadership, encouraging active staff participation and ongoing education [4,5]. Neily and colleagues described teamwork training and use of the checklist which involved 2 months of preparation, 1 day training for operating room teams and 3 monthly coaching interviews over a one year period [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The Royal Australasian College of Surgeons recognized its importance and adopted an amended version for use in Australia and New Zealand. 12 However, the exact mechanism by which SSC improves patient outcomes is poorly understood, with later studies unable to consistently reproduce the marked reduction in mortality and morbidity rates reported in the primary study by WHO. The latest and largest of such studies is the multicenter Canadian study by Urbach et al 11 that assessed 215,000 procedures across 101 hospitals, found that morbidity and mortality only decreased by 0.05% postimplementation.…”
Section: Rationalementioning
confidence: 99%
“…Moreover, are these factors also pertinent in SSCs implemented across Australia and New Zealand? 12 This review aims to assess the implementation of the WHO-adapted SSC within the operating room setting. The primary objective is to compare compliance rates of SSC across specialties and hospitals.…”
Section: Rationalementioning
confidence: 99%
“…La atención en salud involucra un proceso complejo, en el cual factores de la atención como el trabajo en equipo, la comunicación efectiva y el aprendizaje colectivo juegan un papel determinante para lograr el éxito y aportar beneficios al paciente, o, por el contrario, generar riesgos que aumentan la probabilidad de un daño colateral al mismo 3,4 .…”
Section: Introductionunclassified